Mechanisms underlying auditory processing deficits in Fragile X syndrome. Issue 3 (10th February 2020) - McCullagh, Elizabeth A.; Rotschafer, Sarah E.; Auerbach, Benjamin D.; Klug, Achim; Kaczmarek, Leonard K.; Cramer, Karina S.; Kulesza, Randy J.; Razak, Khaleel A.; Lovelace, Jonathan W.; Lu, Yong; Koch, Ursula; Wang, Yuan
Abstract: Autism spectrum disorders (ASD) are strongly associated with auditory hypersensitivity or hyperacusis (difficulty tolerating sounds). Fragile X syndrome (FXS), the most common monogenetic cause of ASD, has emerged as a powerful gateway for exploring underlying mechanisms of hyperacusis and auditory dysfunction in ASD. This review discusses examples of disruption of the auditory pathways in FXS at molecular, synaptic, and circuit levels in animal models as well as in FXS individuals. These examples highlight the involvement of multiple mechanisms, from aberrant synaptic development and ion channel deregulation of auditory brainstem circuits, to impaired neuronal plasticity and network hyperexcitability in the auditory cortex. Though a relatively new area of research, recent discoveries have increased interest in auditory dysfunction and mechanisms underlying hyperacusis in this disorder. This rapidly growing body of data has yielded novel research directions addressing critical questions regarding the timing and possible outcomes of human therapies for auditory dysfunction in ASD.